Dynamic Governance In Public Services Joyoboyo Intermodal Terminal Park And Ride In Surabaya City - Resti Anggraeni, Wanda; Anisykurlillah, Rosyidatuzzahro (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
A large number of private vehicles and limited parking space is one of the traffic problems that cause the emergence of illegal parking spots and vehicles placed haphazardly on the road shoulders and sidewalks, which has an impact on traffic density. The Surabaya City Government, through the Department of Transportation, is presenting an innovation in the form of the Joyoboyo Intermodal Terminal Park and Ride as a form of providing parking space outside the road shoulder and inviting people to switch to using public transportation. This research aims to analyze the application of dynamic governance in the Joyoboyo Intermodal Terminal Park and Ride public services. The research method used in this research is qualitative with a case study approach. Researchers used data collection techniques in the form of observation, interviews, and documentation. The focus of this research uses dynamic governance theory according to Neo Chen (2007) which includes elements of culture, capabilities, and change. Informants in this study were selected purposively and through snowball sampling. The research results show that public services at the Joyoboyo Intermodal Terminal Park and Ride have implemented the concept of dynamic governance in the elements of culture (aspects of relevance and prudence), capabilities (aspects of thinking ahead and thinking again), and change. However, the Transportation Department does not yet have regulations governing the terms of use of the Joyoboyo Intermodal Terminal Park and Ride, so there are often deviations in function by users which can hinder the purpose of building the building